PENGARUH CURRENT RATIO DEBT TO EQUITY RATIO DAN RETURN ON EQUITY RATIO TERHADAP PRICE TO BOOK VALUE PADA PT TELEKOMUNIKASI INDONESIA TBK PERIODE 2014-2023 - Fadil Attaariq, Moh.; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of current ratio, debt to equity ratio, and return on equity partially and simultaneously on price to book value at PT Telekomunikasi Tbk in 2014-2023. The method of research used is quantitative research with a descriptive approach. The population in this research is all financial reports of PT Telekomunikasi Tbk for 2014-2023. The research sample was determined using a purposive sampling technique, namely balance sheet and profit and loss. The data source in this research is secondary data taken from www.telkom.co.id. The data analysis technique in this research uses multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results of the research show that the current ratio obtains a significant value of 0.534 > 0.05, does not have a partially significant effect on price to book value, the debt to equity ratio obtains a significant value of 0.092 > 0.05, does not have a partially significant effect on price to book value, and return on equity obtained a significant value of 0.003 < 0.05, had a partially significant effect on price to book value, and the current ratio, debt to equity ratio, and return on equity obtained a significant value of 0.004 < 0.05 had a significant effect simultaneously on price to book value.